Critical success factor (CSF) for shrub planting works - Ab Sani, Jasasikin; Mohamed Mustafar, Atikah; Ibrahim, Putri Haryati (Universiti Putra Malaysia, 2020)
Quality control plays a vital role in producing an excellent built environment construction work. Landscape development as a major part of the built environment requires at par attentions of quality control in the entire process of development including at the implementation stage. Landscape as an important area in achieving the vision of Malaysia Beautiful Garden in the year 2020 undergoes a long process of development. A thorough monitoring process at the implementation stage is needed to ensure the quality of landscape development end products meets the stakeholders’ satisfaction level. Landscape can be divided into two which are hardscape and softscape. Hardscape refers to a hard element in landscape design that stays the same for years. Whereas, softscape refers to the live horticultural elements of a landscape. Natural environment generates a positive point of view on life, making people feel more active and alive (Wolf & Wohlfart, 2014). This statement illustrates that to create a healthy society, it can begin with enhancing natural environment as to build a positive point of view on life. Shrub is one of the common softscape elements in landscape design. Specific critical success factor (CSF) assessment element for shrub planting should be produced to monitor shrub planting work in landscape construction. This paper is prepared to develop critical success factor for shrub planting works in Malaysia. In this study, 225 respondents among Landscape Architects successfully responded to the survey. The survey began with the assessment elements that had to be rated by respondents according to their general assumptions on the critical level of each element. Finally, this research establishes a set of critical success factor of shrub planting. The result shows that there are eight (8) elements assessment for shrub planting works i.e. overall height, leave, cane, soil mixture, planting hole, root ball size, mulching and planting hole finishing, and treatment. The sum of contribution weightage of CSF overall illustrates that leave stands as the highest score, while mulching indicates the lowest score in critical success factor for shrub planting works.